Process standardization and characterization of Mies: Ethiopian honey wine - Weleba Muesho Gebremichael; Kiros Hagos Abay; Desta Berhe Sbhatu; Goitom Gebreyohannes Berhe; Gebreselema Gebreyohannes (Heliyon)
Mies is a delicious honey wine traditionally processed in Ethiopia and Eritrea. This study aimed to investigate the standardization and characterization of high-quality Mies. The ingredients for Mies preparation were collected, and three formulations were created by varying the amounts of Gesho and honey. First, Birzi was made by dissolving honey in a 1:5 ratio (honey to water) and fermenting it at 22 °C for five days. Next, coarsely ground Gesho was added to the Birzi in plastic tanks, where it fermented for 14 days. The fermented mixture was then filtered through a clean white cotton cloth into a new plastic tank. The filtrate (Mies) was seasoned and fermented for an additional two days, after which its physicochemical, nutritional, sensory, and microbial properties were analyzed using standard methods. As fermentation time increased, the pH values of the three Mies formulations decreased from the first to the twenty-first day. The study revealed that as fermentation time increased, so did the temperature and alcohol levels in all three formulations. Formulation three (F3) was selected by the panelists as the highest quality Mies, with a temperature of 22.50 °C after 21 days. The alcohol content of F3 rose from 2.93 % on the first day to 5.72 % by the twenty-first day. The titratable acidity and total soluble solids of F3 were measured at 3.50 g/L and 26.24 °Brix, respectively. The nutritional contents of F3 included lipid (0.13 %), protein (0.10 %), and carbohydrates (3.02 %). The total energy of F3 was found to be 73.91 %. The study revealed that potassium (K) was the most abundant element in F3 and its ingredients, followed by phosphorus (P), while manganese (Mn) and zinc (Zn) were detected in the lowest amounts. Lactic acid bacteria (LAB) were identified as the predominant microbes in F3. Standardizing production procedures for Ethiopian honey wine can enhance commercialization and scalability, while its distinct flavors and fragrances can boost demand, profitability, and potential market entry. To improve the consistency and quality of honey wine production, further research is required to identify species-specific microbial profiles using molecular tools, optimize production parameters, and address concerns related to preparation.